Consistency and Reconciliation Model In Regional Development Planning - Suryawati, Dina; Helpiastuti, Selfi Budi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
The aim of this study was to identify the problems and determine the conceptual model of regional development planning. Regional development planning is a systemic, complex and unstructured process. Therefore, this study used soft systems methodology to outline unstructured issues with a structured approach. The conceptual models that were successfully constructed in this study are a model of consistency and a model of reconciliation. Regional development planning is a process that is well-integrated with central planning and inter-regional planning documents. Integration and consistency of regional planning documents are very important in order to achieve the development goals that have been set. On the other hand, the process of development planning in the region involves technocratic system, that is, both top-down and bottom-up system of participation. Both must be balanced, do not overlap and do not dominate each other.Â regional, development, planning, consistency, reconciliation